Production of vegetable oil blends and structured lipids and their effect on wound healing - Juliana Neves Rodrigues Ract; Fabiana Andreia Schäfer De Martini Soares; Hosana Gomes Rodrigues; José Ricardo Bortolon; Gilson Masahiro Murata; Maria Inês Almeida Gonçalves; Elaine Hatanaka; Rui Curi; Luiz Antonio Gioielli (Universidade de São Paulo, 2015)
Two oil blends (sunflower/canola oils 85/15 (BL1) and canola/linseed oils 70/30 (BL2)), were prepared and enzymatically interesterified to be applied to surgically-induced wounds in rats. Following surgery, the animals were submitted to the Treatment with Physiological Saline (TPS) (control group), Blends (TBL), and Structured Lipids (TSL). The control group (TPS) received physiological saline solution for 15 days. In TBL, BL1 was administered during the inflammation phase (days 0-3) and BL2 in the tissue formation and remodeling phase (days 4-15). In TSL, Structured Lipid 1 (SL1) and Structured Lipid 2 (SL2) were used instead of BL1 and BL2, respectively. The aim of this study was to compare wound closure evolution among rats treated with the blends or structured lipids versus control rats treated with physiological saline. The wound healing process was evaluated by measuring the wound areas along the treatments and the concentrations of cytokines. An increase in the areas of wounds treated with the blends and structured lipids in the inflammatory phase was observed, followed by a steeper closure curve compared to wounds treated with physiological saline. The changes observed during the inflammatory phase suggest a potential therapeutic application in cutaneous wound healing which should be further investigated.